Who was Peter Karlsson of Helsingborg? An Attempt to Identify a Medieval Seal Stamp Find - Weidhagen-Hanerdt, Margareta; Sjøvold, Torstein; Mörnstad, Håkan (Current Swedish Archaeology, 1996)
Finds of seal stamps in graves from the Middle Ages are very rare, especially if they are undamaged. The owner of the well-preserved stamp in grave 207 in the Church of St. Clement in Helsingborg was a nobleman, called Peter Karlsson. His coat of arms, which is quartered, restricted the searching for his relationships geographically. A ’terminus ante quem’ was set by the archaeological investigation. The individual age was determined by means of an osteological and odontological investigation. It has not, on the whole, been possible to connect the actual name with any known armorial seal with the quartered shield. The unclear family relationships of this time and the only accidentally preserved documents from the Middle Ages do not offer the research worker of genealogy and heraldry sufficiently reliable sources. Even if there is no clear evidence, however, many facts nevertheless support the presumption that the seal owner in grave 207 was identical with Mayor Peter Karlsson of Helsingborg and also that he was a member of the Thott family.